Las fronteras de la política. La vida política amenazada según Isócrates y Demóstenes - Sancho Rocher, Laura (Gerión. Revista de Historia Antigua, 2002)
In this article I try to compare the two thinkers in respect to their attitude to Philipp II and monarchy. Even though the both have different ideas about the actual athenian democracy, in respect to tyranny and dynasteia there’s wide agreement between them, because Isocrates and Demosthenes prefer any politeia of citizens than a monarchy without politeia.